Amygdala subnucleus volumes in psychosis high-risk state and first-episode psychosis - Reetta-Liina Armio; Heikki Laurikainen; Tuula Ilonen; Maija Walta; Raimo K. R. Salokangas; Nikolaos Koutsouleris; Jarmo Hietala; Lauri Tuominen (Elsevier B.V., 2025)
Structural and functional abnormalities of the amygdala in schizophrenia have been well documented. Post-mortem studies suggest that the lateral nucleus is particularly affected in schizophrenia. It is not known whether the amygdala subnuclei are differently affected at the time of the first-episode psychosis or already at high-risk state.
75 first-episode psychosis patients (FEP), 45 clinical high-risk patients (CHR) and 76 population controls participated in this cross-sectional case-control study. Participants underwent T1-weighted 3T MRI scans, from which the amygdala was segmented using a newly developed automated algorithm. Because early adverse events increase risk for psychosis and affect the amygdala, we also tested whether experiences of childhood maltreatment associate with the putative amygdala subnuclei abnormalities.
Compared to the population controls, FEP had smaller volumes of the lateral, and basal nuclei. In CHR, only the lateral nucleus was significantly smaller compared to the control subjects. Experience of childhood maltreatment was inversely associated with lateral nucleus volumes in FEP but not in CHR.
These results show that the lateral and basal nuclei of the amygdala are already affected in FEP. These volumetric changes may reflect specific cellular abnormalities that have been observed in post-mortem studies in schizophrenia in the same subnuclei. Decreased volume of the lateral nucleus in CHR suggest that a smaller lateral nucleus could serve as a potential biomarker for psychosis risk. Finally, we found that the lateral nucleus volumes in FEP may be sensitive to the effects of childhood maltreatment.